2019
DOI: 10.1016/j.cels.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Inference of Direct Interactions in Large-Scale Ecological Networks from Heterogeneous Microbial Sequencing Data

Abstract: Highlights d FlashWeave infers direct associations, resulting in sparse, interpretable networks d The method's flexible graphical model framework scales to 500,000+ samples d It integrates environmental & technical factors; adjusts for specific latent signals d An extensive human gut microbial network reveals patterns of biological interest

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 68 publications
1
113
0
Order By: Relevance
“…Co-occurrence networks were constructed using filtered ASV occurrence data sets in which the ASV were filtered to only those that were present in at least five samples resulting in a 102 ASV data set. The 102 x 63 matrix was provided as input to FlashWeave v1.0 (74) using default parameters, and visualized in Gephi v. 0.9.2 (75). Then to consider whether the ASVs in the Core80, Dynamic50, or Variable fractions of the SaM were affiliated with particular levels of PalA in the ascidian lobes, PalA niche robust optimum and range were computed using the occurrence and dry weight normalized contextual data (76).…”
Section: Methodsmentioning
confidence: 99%
“…Co-occurrence networks were constructed using filtered ASV occurrence data sets in which the ASV were filtered to only those that were present in at least five samples resulting in a 102 ASV data set. The 102 x 63 matrix was provided as input to FlashWeave v1.0 (74) using default parameters, and visualized in Gephi v. 0.9.2 (75). Then to consider whether the ASVs in the Core80, Dynamic50, or Variable fractions of the SaM were affiliated with particular levels of PalA in the ascidian lobes, PalA niche robust optimum and range were computed using the occurrence and dry weight normalized contextual data (76).…”
Section: Methodsmentioning
confidence: 99%
“…The lack of null model and/or statistical test on these observations, however, did not allow to determine whether biologic or random processes were responsible of the patterns. In a more recent study, global gut microbiome co-occurrence networks were found to have significant higher phylogenetic assortativity than in randomize networks overall (Tackmann, Matias Rodrigues, & von Mering, 2019), while size effect was not quantified at distinct distance classes and no interpretation was provided on these observations. Our new approach has the potential to uncover inter-dependencies between phylogenetic relatedness and co-occurrence and co-exclusion of any micro-organisms in any environment.…”
Section: Discussionmentioning
confidence: 94%
“…There are multiple methods to determine associations (normally based on correlations) between microorganisms using their abundances (e.g. eLSA Xia et al (2011Xia et al ( , 2012, CoNet Faust and Raes (2016), SPIEC-EASI Kurtz et al (2015), or FlashWeave Tackmann et al (2019)). These abundance-based associations compose a network, where nodes represent microorganisms and edges represent either co-presence (positive association) or mutual exclusion (negative association) relationships, which constitute microbial interaction hypotheses.…”
Section: Association Network To Generate Microbial Interaction Hypotmentioning
confidence: 99%